The impact of using small-sided games on teaching basic handball skills to students of the College of Sports Sciences at Mu’tah University - Sha’lan, Maen Ahmad Mahmoud (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to identify the effect of using small-sided games on teaching basic handball skills to students of the College of Sports Sciences at Mutah University, using the experimental method. The study sample consisted of 20 students from the College of Sports Sciences at Mu’tah University who were enrolled in the handball course. They were selected using the purposive method and divided into two equal groups (experimental group = 10 students, and control group = 10 students). An educational program was prepared using small-sided games to teach basic handball skills. The program was implemented during eight weeks, with three meetings per week. The data were processed through the Statistical Package for the Social Sciences (SPSS). Our results showed that using small-sided games in teaching basic skills in handball has a positive impact on improving the level of performance of learners (p<0.05). Therefore, the authors recommend to use small-sided games in teaching basic skills in handball.